Posttranslational proteolytic processing of Leda-1/Pianp involves cleavage by MMPs, ADAM10/17 and gamma-secretase - Biswas, Siladitta; Adrian, Monica; Winkler, Manuel; Géraud, Cyrill (Biochemical and biophysical research communications, 2016)
Leda-1/Pianp is a type I transmembrane protein expressed by CNS cells, murine melanoma cell line B16F10 and rat liver sinusoidal endothelial cells. The early steps of posttranslational modifications of Leda-1/Pianp have been described to include glycosylation and processing by proprotein convertases. Here, we comprehensively characterized the subsequent steps of proteolytic processing of Leda-1/Pianp. For this purpose specific protease inhibitors and cell lines deficient in PS1, PS2, PS1/PS2 and ADAM10/17 were deployed. Leda-1/Pianp was cleaved at numerous cleavage sites within the N-terminal extracellular domain. The sheddases involved included MMPs and ADAM10/17. Ectodomain shedding yielded C-terminal fragments (CTF) of ∼15 kDa. The CTF was further processed by the γ (gamma)-secretase complex to generate the intracellular domain (ICD) of ∼10 kDa. Although PS1 was the dominant intramembrane protease, PS2 was also able to cleave Leda-1/Pianp in the absence of PS1. Thus, Leda-1/Pianp is constitutively processed by proprotein convertases, sheddases including MMPs and ADAM10/17 and intramembrane protease γ-secretase.
Gesehen am 31.07.2019
Available online 24 June 2016